Nanoparticle synthesis and the addition of group IV elements for the destabilisation of magnesium hydride - Chaudhary, Anna-Lisa (Curtin University, 2013)
This thesis explores hydrogen storage in magnesium for the goal of producing clean energy. Si nanoparticles were synthesised, then mixed with MgH2 to improve desorption. MgH2 and Si mixtures were desorbed and compared with the synthesised nano-silicon kinetics. Mg2Si nanoparticles were synthesised and high pressure hydrogenation attempted. Finally, the addition of Si, Ge and Sn to Mg-based hydrides led to the successful destabilisation of MgH2 and NaMgH3 resulting in improved hydrogen release at lower temperatures.